The Optimal Suture Placement and Bone Tunnels for TFCC Repair: A Cadaveric Study - Matsumoto, Taiichi; Tang, Peter; Fujio, Keiji; Strauch, Robert J.; Rosenwasser, Melvin P. (Journal of Wrist Surgery, 2018)
Background Transosseous repair of foveal detachment of the triangular fibrocartilage complex (TFCC) is effective for distal radioulnar joint stabilization. However, studies of the optimal foveal and TFCC suture positions are scant.Purpose The purpose of this study was to clarify the optimal TFCC suture position and bone tunnels for transosseous foveal repair.Materials and Methods Seven cadavers were utilized. The TFCC was incised at the foveal insertion and sutured at six locations (TFCCs 1–6) using inelastic sutures. Six osseous tunnels were created in the fovea (foveae 1–6). Fovea 2 is located at the center of the circle formed by the ulnar head overlooking the distal end of the ulna (theoretical center of rotation); fovea 5 is located 2 mm ulnar to fovea 2. TFCC 5 is at the ulnar apex of the TFCC disc; TFCC 4 is 2 mm dorsal to TFCC 5. TFCC 1 to 6 sutures were then placed through each of the six osseous tunnels, resulting in 36 combinations, which were individually tested. The forearm was placed in five positions between supination and pronation, and the degree of suture displacement was measured. The position with the least displacement indicated the isometric point of the TFCC and fovea.Results The mean distance of suture displacement was 2.4 ± 1.6 mm. Fovea 2, combined with any TFCC location, (0.7 ± 0.6 mm) and fovea group 5, combined with TFCC 4 location (0.8 ± 0.8) or with TFCC 5 location (0.9 ± 0.6) had statistically shorter suture displacements than any other fovea groups.Conclusion For TFCC transosseous repair, osseous tunnel position was more important than TFCC suture location.
Keywords: triangular fibrocartilage complex; foveal; transosseous repair; cadaveric; optimal suture location